Geomorphological of a portion of the Andes and Pre-Andes of San Juan, Argentina - Esper Angillieri, María Yanina (2013)
A detailed geomorphological map is presented for a portion of a poorly investigatedmountainous region of the Dry Frontal Andes and Western Pre-Andes of San Juan provincearound 30S latitude. This map shows the presence and extension of landforms andgeomorphic processes in an area of 2175.9 km2 and is the result of detailed aerialphotograph and remotely sensed data interpretation, including digital elevation models,supported by field survey. The landforms have been distinguished according tomorphogenetic criteria, into: (i) glacial landforms; (ii) periglacial landforms; (iii) massmovement landforms; (iv) fluvial landforms: (v) polygenic landforms and (vi) neotectoniclandforms. The objective of this map is to provide information on the landforms present inthe selected area, allowing it to be used as a baseline for the study of landscape evolution orsupport guidelines for territorial management and planning.